2020
DOI: 10.1097/aog.0000000000003862
|View full text |Cite
|
Sign up to set email alerts
|

Internal Version Compared With Pushing for Delivery of Cephalic Second Twins

Abstract: OBJECTIVE: To assess neonatal morbidity and mortality according to whether cephalic second twins were born after internal version followed by total breech extraction or after instructions to push. We hypothesized that interval version would result in shorter intertwin delivery intervals and lower cesarean delivery rates for the second twin and therefore better neonatal outcomes. METHODS: These planned analyses of the JUMODA (JUmeaux MODe d'Accouchement)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…are guided by a pragmatic view about cervical ripening, such as all large prospective observational studies in obstetrics [30][31][32][33]. These studies allow multiple analyses of data and conclusions about pragmatic management and consequences of some current obstetric conditions that were not adapted to randomized controlled trials (i.e., twins with The JUmeaux MODe d'Accouchement (JUMODA) study) [30,[34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…are guided by a pragmatic view about cervical ripening, such as all large prospective observational studies in obstetrics [30][31][32][33]. These studies allow multiple analyses of data and conclusions about pragmatic management and consequences of some current obstetric conditions that were not adapted to randomized controlled trials (i.e., twins with The JUmeaux MODe d'Accouchement (JUMODA) study) [30,[34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, some have advocated that breech extraction may even offer better results when the second twin is in a cephalic presentation, 57 yet a recent sub-analysis of the JUMODA study of more than 4,000 second twins have concluded that internal version followed by total breech extraction of the cephalic second twin is not associated with better neonatal outcomes than pushing. 58 Breech extraction is accomplished in the manner described by Rabinovici et al: 59 the feet of the second fetus are grasped through the intact membranes, without rupturing the amniotic sac. Gentle, continuous traction is exerted on both feet toward the birth canal.…”
Section: Delivery Of the Second Twinmentioning
confidence: 99%
“…On the other hand, the obstetrical skills in internal podalic version, breech extraction, and operative vaginal deliveries for twin delivery tend to disappear due to ongoing debates about the better route of delivery for twins, singleton breech fetuses, or the safety of assisted delivery [2]. There is consistent data supporting active management of the second twin delivery: the reduction of the inter-twin delivery interval could improve neonatal outcomes [3]. Even in the case of cephalic/cephalic twin presentations, 20% of vertex presenting second twins will change presentation spontaneously after the first twin is delivered requiring obstetrical maneuvers [4].…”
Section: Introductionmentioning
confidence: 99%